Development of a stratospheric airship-based network architecture for telecommunication in remote areas - Abdullayev, Mukhit; Kuttybayeva, Ainur; Tazhen, Kalmukhamed; Khabay, Anar; Ospanova, Nurzhamal; Tashtay, Yerlan; Sabyrbayev, Arnur; Samat, Iliyas; Abdykadyrqyzy, Rimma; Zhumakhanova, Daria (Eastern-European Journal of Enterprise Technologies, 2025)
The object of this study is a stratospheric airship-based telecommunication platform, employed as a high-altitude platform station (HAPS), designed to operate at altitudes of 20–30 km and provide broadband connectivity in regions with limited terrestrial infrastructure such as rural and remote areas of the Republic of Kazakhstan. The key research problem is to ensure stable connectivity of HAPS-based telecommunication platforms under strong stratospheric winds, with limited payload capacity and energy resources, while developing a scalable network architecture for multi-airship coordination. This paper proposes a network concept based on modular nano-airships, which reduces drag, enhances maintainability, and ensures continuous service. Calculations of lifting capacity, aerodynamic drag of different envelope shapes, energy balance, and the coverage radius of a single station were performed. Experimental tests of a prototype confirmed the feasibility of using the sub-GHz band (433 MHz) to provide long-range communication under ground test conditions, where signal attenuation was found to be minimal compared to higher frequencies. Due to the obtained characteristics, the hypothesis of employing a group of smaller airships instead of a single large carrier was confirmed. This is explained by their reduced sensitivity to wind loads, flexibility in network configuration, and lower operational risks. Unlike traditional satellite systems, which are expensive to launch and maintain, stratospheric airships can be recovered, repaired, and redeployed at relatively low cost, offering an economically viable solution for developing regions. The results can be applied in the creation of national communication networks for remote and sparsely populated areas of the Republic of Kazakhstan, in emergency response operations, and as a complementary layer to satellite constellations. The proposed concept demonstrates that modular HAPS networks are a realistic and scalable alternative, capable of providing broadband access under real-world atmospheric and geographic constraints